Study of the Arrhythmogenic Profile of Dogs with Myxomatous Mitral Valve Disease in Stages B1 and B2 - Santos, Beatriz Almeida [UNESP]; Corrêa, Jaqueline Valença [UNESP]; Latini, Carolina Dragone [UNESP]; Tsunemi, Miriam Harumi [UNESP]; Alfonso, Angélica [UNESP]; Machado, Luiz Henrique de Araújo [UNESP]; Lourenço, Maria Lucia Gomes [UNESP] (My University, 2024)
Myxomatous mitral valve disease (MMVD) is the most prevalent cardiac disease in dogs. This study aimed to compare the arrhythmogenic profile and heart rate variability (HRV) of dogs with MMVD in stages B1 and B2. Electrocardiographic exams and the medical records of 60 dogs were analyzed, and HRV, P wave dispersion, QT interval dispersion, and QT interval instability parameters were determined. The results showed significantly increased values in stage B2 compared with stage B1 (p < 0.05) regarding P wave maximum and minimum duration (Pmax and Pmin) and short-term instability (STI). In contrast, no statistically significant differences were observed regarding HRV parameters, P wave dispersion, or QT interval dispersion. Our findings showed that cardiac remodeling in stage B2 could not significantly alter the sympathovagal balance and showed little interference with the predisposition of arrhythmias in dogs with MMVD.
Keywords: arrhythmogenesis; mitral valve disease; sympathovagal homeostasis